Crossing Organizational Boundary’s Effect on Paradigmatic Shift and the Implication to Marketing Strategy of an Organization - Fahrina Mustafa; Riad Mustafa (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2018)
This paper studies the paradigmatic shift as the effect on the crossing organizational boundaries activities. Boundary crossing as part of specific function of organizations is common to organization theories. Nevertheless, the increasing and strong rate of occurrence of the crossing boundary activities is considered important today as the consequence of the technological revolution in information and communication technology coupled with the future technologies. Crossing boundaries influence the people involved and the institutional sets. The relationships within the boundaries are increasingly dynamic. Hence, this, in turn, may lead to paradigmatic shift. From the perspective of organization and innovation studies these processes are to a great extent attractive since they may create different conditions the existing literatures on organization as well as innovation, and consequently, on marketing. Therefore, this paper aims at studying the marketing strategy response of an organization by identifyingstates that emerge or condition that may be created as the paradigms shifted.